Pengaruh Integritas Mahasiswa Dan Kepercayaan Diri Terhadap Perilaku Kecurangan Akademik Dimasa Pandemi Covid-19 Dengan Motivasi Belajar Sebagai Variabel Intervening - Gaspersz, Jefry; Sososutiksno, Christina (Program Pascasarjana STIE Amkop Makassar, 2023)
Abstract This study aims to empirically examine the effect of student integrity and self-confidence on academic fraud behavior during the covid-19 pandemic with learning motivation as an intervention variable. This research is a quantitative research using primary data, this data was obtained from respondents through a questionnaire which was distributed to 89 student majoring in accounting. The population in this study were accounting students from the 2018-2019 class. Data analysis used SPSS 24 for windows. The results of the study show that student integrity and self-confidance affects academic fraud behavior during the covid-19 pandemic, learning motivation was unable to mediate the relationshop between student integrity and self-confidence on academic fraud behavior. Keywords: Student Integrity, Self Confidance, academic fraud behavior, learning motivation..